APLIKASI PETRI NET PADA SISTEM PEMBAYARAN TAGIHAN LISTRIK PT. PLN (Persero) RAYON AMBON TIMUR - Wattimena, Freya N.; Pentury, Thomas; Lesnussa, Yopi A. (PATTIMURA UNIVERSITY, 2012)
Petri Net is a model of Mathematics used in the system event discrit to illustrate certain event. One application of Petri Nets is to sketch the entrance occurs in a place like the public service system. This reserce will simply describe the use of Petri Net to sketch the entrance occurs in electricity bill payment system of PT.PLN (Persero) Rayon Ambon Timur by the number of place is 7 and the transition is 8, and to determine the matrix representation and the coverability tree of the model.